Bionics as the New Required Vector of Development - Chizhov A. A. (Interactive science, 2020)
the article analyzes and summarizes the principles of architectural bionics applied to various construction and technical structures. The analysis was carried out in the course of studying the scientific literature on the topic “Bionics. Architectural structures». The purpose of this work is to study the principles of architectural bionics, to study the possibility and effectiveness of their application for solving engineering and technical problems. The main task of the work was to study the directions and principles of development of architectural bionics, to assess the effectiveness of their application for solving technical problems, to find the correspondence of biological systems to construction and technical structures and facilities, to analyze known architectural structures from the point of view of architectural bionics.
Keywords: биология; ритм; бионика; конструкции; пластика; biology; rhythm; живые организмы; пропорция; устройства; нейробионика; архитектурно – строительная бионика; основные теоретические положения; методика архитектурно – бионического моделирования; проблемы формообразования живой природы; природные проявлений гармонии; симметрия – асимметрия; тектонические формы живой природы; bionics; living organisms; structures; devices; neurobionics; architectural and construction bionics; basic theoretical provisions; methods of architectural and bionic modeling; problems of formation of wildlife; natural manifestations of harmony; plastic; proportion; symmetry-asymmetry; tectonic forms of wildlife